Voicing produced by a constant velocity lung source - Howe, M. S. (Acoustical Society of America, 2013)
An investigation is made of the influence of subglottal boundary conditions on the prediction of voiced sounds. It is generally assumed in mathematical models of voicing that vibrations of the vocal folds are maintained by a constant subglottal mean pressure p(I), whereas voicing is actually initiated by contraction of the chest cavity until the subglottal pressure becomes large enough to separate the vocal folds. The problem is reformulated to determine voicing characteristics in terms of a prescribed volumetric flow rate Q(o) of air from the lungs—the evolution of the resulting time-dependent subglottal mean pressure [Formula: see text] is then governed by glottal mechanics, the aeroacoustics of the vocal tract, and the influence of continued contraction of the lungs. The new problem is analyzed in detail for an idealized mechanical vocal system that permits precise specification of all boundary conditions. Predictions of the glottal volume velocity pulse shape are found to be in good general agreement with the traditional constant-p(I) theory when p(I) is set equal to the time averaged value of [Formula: see text]. But, in all cases examined the constant-p(I) approximation yields values of the mean flow rates Q(o) and sound pressure levels that are smaller by as much as 10%.